Abnormalities in T cell subsets in the circulating immunity and tumor microenvironment in patients with pancreatic ductal adenocarcinoma - SU Bingwei, SHEN Baiyong (Waike lilun yu shijian)
Pancreatic ductal adenocarcinoma (PDAC) is a highly malignant solid tumor of digestive system, which can affect the immune system. The abnormalities of distribution, percentage, function, and activity of immune cells in both peripheral circulation and tumor microenvironment (TME) are detected in patients with PDAC. T cells are the main lymphocytes that participate in cell-mediated immunity and exert anti-tumor effects. According to the function and the cluster of differentiation, T cells can be divided into different subsets, such as CD4+, CD8+, CD4+ CD25+, etc. The abnormalities of T cell subsets in the circulating immunity and TME of patients with PDAC may play an important role in cancer progress.